Polyphenol oxidase from soybeans (glycine max v. palmetto) and its respoftse to copper and other micronutrients - Marziah, Mahmood; Lam, Chee H. (Informa UK Limited, 1987)
Copper deficiency in soybeans does not readily exhibit visible symptoms. However, it has a profound effect on the activities of polyphenol oxidase (PPO, O-diphenol : oxygen oxidoreductase, E.C.1.10.3.1) that is present in the young leaf extracts. Polyphenol oxidase activity was completely absent in minus copper plants grown in solution culture in the glasshouse. Similarly, copper-deficient plants grown in peat soils had very low PPO activity. The enzyme, on the other hand, increased in activity as the supply of cooper to the plants was increased. Deficiencies in other micronutrients (B, Co, Fe, Mn, Mo, Zn) did not significantly lower the enzyme activity. Since very little or no activity was detected in leaf extracts from all copper-deficient treatments, this indicates that the enzyme may be used to diagnose Cu deficiency in soybean.